Pengaruh Brand Awarness, Brand Image, dan Brand Trust terhadap Brand Loyalty pada Pelanggan Produk Kosmetik Make Over di Kota Surabaya - Rohma Kusuma Zulianti; Jojok Dwiridotjahjono (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The aim of this research is to determine and assess the influence of brand awareness, brand image and brand trust on brand loyalty among cosmetics buyers in Surabaya. This research focuses on people who buy cosmetic goods in Surabaya. The sample size was 100 participants, taken using purposive and cluster sampling procedures. This research data was analyzed using the "multiple regression" technique from SPSS 27. The results of the analysis show that: 1. Brand awareness, brand image and brand trust have a big influence on brand loyalty among Surabaya cosmetic buyers; we find that both have a strong influence on loyalty. Among cosmetic buyers in Surabaya, 3. The brand image of cosmetic buyers in Surabaya has a certain influence on brand loyalty. 4. To some extent, brand trust has a major impact on the brand. Loyalty of Makeup Cosmetics Buyers in Surabaya.